Handbook of Autopsy Practice - Waters, Brenda L. (Humana Press : Imprint: Humana, 2009)
Handbook of Autopsy Practice, Fourth Edition is a testament to the continued evolution of autopsy pathology. In this updated and expanded new edition, the editors cover technological advancements and discuss skills that are necessary in order to perform the most efficient autopsy possible. These skills include efficient and safe dissection techniques, appropriate handling of unexpected findings, meticulous written and photographic documentation, accurate interpretation of findings and finally, timely, compassionate and professional communication with families, physicians and legal counsel. Handbook of Autopsy Practice, Fourth Edition is divided into three parts. Part I contains six new chapters in which the reader will find an assortment of tools that will increase the value of the autopsy. Included in the section are valuable resources and tools such as a sample next-of-kin letter, a quality assurance worksheet, new discourse on the dissection procedure which is accompanied by a worksheet and template for the gross description. There is also a new, detailed discussion of the safe handling of sharps, complete with photographs and the reader will also find the updated requirements of the Eye Bank of America and the U.S. Food and Drug Administration for ocular tissue transplantation. Part II has been updated with new diseases and recent references added. Practicing autopsy pathologists, residents and students are invited to review this alphabetical listing of disorders before each autopsy in order to re-acquaint themselves with what they might encounter. Part III provides a series of tables providing organ weights and body measurements for fetuses, children and adults. Handbook of Autopsy Practice Fourth Edition is an essential resource for clinicians, pathologists, residents and students who strive to hone their trade and increase the value of the autopsies they perform.